2015
DOI: 10.1371/journal.pone.0134499
|View full text |Cite|
|
Sign up to set email alerts
|

Carbonic Anhydrase Protects Fatty Liver Grafts against Ischemic Reperfusion Damage

Abstract: Carbonic anhydrases (CAs) are ubiquitous metalloenzymes that catalyze the reversible hydration of carbon dioxide to bicarbonate and a proton. CAs are involved in numerous physiological and pathological processes, including acid-base homeostasis, electrolyte balance, oxygen delivery to tissues and nitric oxide generation. Given that these processes are found to be dysregulated during ischemia reperfusion injury (IRI), and taking into account the high vulnerability of steatotic livers to preservation injury, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…This is in line with our previous observation showing that CA II addition to the IGL-1 solution prevented IRI in steatotic livers, which was associated with an enhanced CA II expression (Bejaoui et al, 2015). Thus, the AZ protective mechanism may be related to enhanced CA II protein expression rather than CA hydratase activity inhibition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with our previous observation showing that CA II addition to the IGL-1 solution prevented IRI in steatotic livers, which was associated with an enhanced CA II expression (Bejaoui et al, 2015). Thus, the AZ protective mechanism may be related to enhanced CA II protein expression rather than CA hydratase activity inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm that AZ pretreatment at the dose of 30 mg/kg was efficient to inhibit CA hydratase activity (0.103 6 0.034 in the IGL-1 group versus 0.020 6 0.007 WAU/mg protein in the AZ group). Moreover, we examined the potential effect of AZ in the regulation of CA II expression, as we have previously shown that CA II addition to the IGL-1 solution protects steatotic livers against IRI (Bejaoui et al, 2015). Surprisingly, we observed that AZ induced a significant induction of CA II protein levels (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Other natural AMPK activators, such as 3,5,4′-trihydroxy- trans -stilbene (resveratrol) [ 63 ], could be good candidates as additives for preservation solutions in future approaches. This principle also applies to PEG35 solutions, in which there has been an increase in activated AMPK under hypoxic conditions [ 64 , 65 , 66 ]. The mechanisms by which PEG35 activates AMPK in IGL-1 and rinse solutions remain to be investigated in depth.…”
Section: New Additives For Improving Cold Static Preservation: Oxygen...mentioning
confidence: 99%
“…It is also metabolizing many drugs, medications, chemicals, and natural substances. Although several CA isoforms, including CA I, CA II, CA III, CAVII and CA IX, have been described in liver, there is very limited information about regulation of CAs at the gene and protein levels, especially their transcriptional regulation [4,[42][43][44].…”
Section: Comparison Of Gene Expression Levels Of Control and Mutant G...mentioning
confidence: 99%